(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2016)
Thalassemia is a wide range hereditary disease with high incidence in Egypt along with the high frequency of consanguineous marriages. Investigation the heterogeneity, molecular basis, and natural history are the most effective methods to deal with the thalassemia to develop effective method for management and prevention including the prenatal diagnosis. The current study aims to detect the most common Î² -globin gene mutations in Egypt among Î²-thalassemic patients by using PCR based reverse hybridization method (StripAssay) for the most prevalent 22 Î²-globin gene mutations in the Mediterranean population in an attempt to estimate the incidence of each mutation, and an attempt to improve our control strategy of Î²- thalassemia. This study included a total of 37 confirmed Î²- thalassemia ethnic Egyptian patients (23 males and 14 females) out of them 17 patients were a thalassemia major and 20 were a thalassemia intermediate. Evaluation of Î²-thalassemia mutations revealed that, the presence of 9 different Î²-globin mutations. The most frequent mutation was IVS 1-110[34%], IVS 1-6(23.5%), IVS 1-1(19%), Codon 27[6.5%], IVS 2-848[6.5%], IVS 2-745[2.1%] and IVS 2.1 [2.5%], Codon 39[4%]), and IVS 1.5 [1.5%]. IVS 1-110[G>A] is the commonest homozygous mutation found in 6 out of 14 homozygous cases accounting for about 43% of homozygous mutations while, IVS 1-110[G>A]/ IVS 1-6[T>C] is the commonest heterozygous mutation found in 6 out of 23 heterozygous cases accounting for about 26% of heterozygous mutations. In conclusion, Î²-Globin Strip Assay is useful rapid screening method for Î²-globin gene mutations which can provide an insight into the detection of individual patients, to take the proper measurement, and thus could be used as a basis for genetic counseling and prenatal diagnosis.